2018
DOI: 10.1113/jp276798
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle ceramides and relationship with insulin sensitivity after 2 weeks of simulated sedentary behaviour and recovery in healthy older adults

Abstract: Older adults are at risk of physical inactivity as they encounter debilitating life events. It is not known how insulin sensitivity is affected by modest short-term physical inactivity and recovery in healthy older adults, nor how insulin sensitivity is related to changes in serum and muscle ceramide content. Healthy older adults (aged 64-82 years, five females, seven males) were assessed before (PRE), after 2 weeks of reduced physical activity (RA) and following 2 weeks of recovery (REC). Insulin sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 52 publications
3
53
0
Order By: Relevance
“…The primary aim of this research was to examine changes in systemic insulin sensitivity and relate changes in insulin sensitivity to the level of pro-inflammatory ceramides in skeletal muscle. Reidy et al (2018) corroborated earlier reports and found that insulin sensitivity significantly decreased following 2 weeks of physical inactivity. Interestingly, after 2 weeks of returning to a physically active state, insulin sensitivity had rebounded above baseline levels by 14%.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The primary aim of this research was to examine changes in systemic insulin sensitivity and relate changes in insulin sensitivity to the level of pro-inflammatory ceramides in skeletal muscle. Reidy et al (2018) corroborated earlier reports and found that insulin sensitivity significantly decreased following 2 weeks of physical inactivity. Interestingly, after 2 weeks of returning to a physically active state, insulin sensitivity had rebounded above baseline levels by 14%.…”
supporting
confidence: 92%
“…Reidy et al . () corroborated earlier reports and found that insulin sensitivity significantly decreased following 2 weeks of physical inactivity. Interestingly, after 2 weeks of returning to a physically active state, insulin sensitivity had rebounded above baseline levels by 14%.…”
supporting
confidence: 92%
“…Subject characteristics have been outlined previously . Healthy older adults (5F/7M, 70 ± 2 years, BMI of 26 ± 1, 92 ± 2 mg/dL resting glucose, HbA1c % 5.5 ± 0.1, 31 ± 2% fat and 49 ± 3 kg of total lean mass) participated in the study.…”
Section: Resultsmentioning
confidence: 99%
“…We recruited 12 (seven male, five female) healthy, community‐dwelling, glucose tolerant subjects from the Salt Lake City area between the ages of 60 and 85 years and with a BMI <30 kg/m 2 . Healthy subjects were recruited and screened similarly as we have previously reported . All subjects read and signed the informed consent form.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation